2013
DOI: 10.1177/2151458513502038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Emergency Department Length of Stay for Patients With Hip Fracture

Abstract: Time to surgery, which includes time in the emergency department (ED), is important for all patients with hip fracture. We hypothesized that patients with hip fracture spend significantly more time in the ED than do patients with the top 5 most common conditions. In addition, we hypothesized that there are patient, physician, and hospital factors that affect the length of time spent in the ED. We retrospectively reviewed our institution's hip fracture database and identified 147 elderly patients with hip fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations. Other characteristics . Of the seven American studies that considered insurance status, most found longer stays among uninsured patients8 14 17 34 38 or those without private insurance,12 and two also found longer stays among Medicaid patients;14 38 one study of non-admitted patients reported that only Medicare patients had longer LOS 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations. Other characteristics . Of the seven American studies that considered insurance status, most found longer stays among uninsured patients8 14 17 34 38 or those without private insurance,12 and two also found longer stays among Medicaid patients;14 38 one study of non-admitted patients reported that only Medicare patients had longer LOS 19.…”
Section: Resultsmentioning
confidence: 99%
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations.…”
Section: Resultsmentioning
confidence: 99%
“…This study analyzed the main and interaction effects of 4 determinants of ED-LOS (gender, age, mode of arrival, and clinical acuity). Previous studies have used various methodologies to study the main effects of different variables on ED-LOS: chi-square tests 6,7,8,11,16,18,19,25,26,27,28,30,32,37 multiple linear regression, 10,12,13,20,22,23,24,26,36,39 log linear regression, 21 multilevel hierarchical analysis, 9,35,40 autoregression models, 31 simple/multivariate logistic regression models, 11,14,17,24,25,34,43 ANOVA, 5,6,32 and the Cox proportional hazard model. 29,33 However, the literature lacks studies of the interaction effects of 2 or more factors.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in a busy hospital, the length of time spent in the ED may be considerably longer. 25 Lack of appropriate triage will lengthen the stay in the ED, especially for an elderly patient who does not appear to require acute care. In addition, the environment is frequently noisy, seemingly chaotic, and often confusing and frightening for the elderly patient and promotes the development of delirium.…”
Section: Hip Fractures Stephen Kates MDmentioning
confidence: 99%